Návrhy na rozšíření marketingové komunikace společnosti pro mezinárodní publikum společnosti - Ulrichová, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Diplomová práce je zaměřena na společnost, která je přední českou firmou prodávající český design a zároveň organizací pořádající mezinárodní designové soutěže. Cílem diplomové práce je na základě analýz současného marketingového postavení společnosti připravit vlastní návrhy a doporučení, které povedou ke zvýšení povědomí nejen o produktech společnosti Czechdesign, ale i e-shopu v mezinárodním měřítku.

The diploma thesis is focusing on a company that is a leading Czech company selling Czech design and also an organization hosting international design competitions. The aim of the thesis is, based on the analyses of the current marketing position of the company, to prepare own proposals and recommendations that will lead to an increase in awareness of the company Czechdesign products and e-shop internationally.
Proposals for Expanding the Marketing Communication for a Company’s International Audience
Keywords: Marketing; komunikace; sociální media; mezinárodní publikum; český design; Marketing; communication; social media; international audience; Czech design